Development of Growth Theory for Vapor–Liquid–Solid Nanowires: Wetting Scenario, Front Curvature, Growth Angle, Linear Tension, and Radial Instability - Valery A. Nebol’sin; Nada Swaikat; Alexander Yu. Vorob’ev (Journal of Nanotechnology)
In this paper, we report that under wetting conditions (or modes) of nanowire (NW) growth, when a nonplanar crystallization front emerges under a catalyst droplet, a shift in the three-phase line (TPL) of the vapor–liquid–crystal interface occurs under thermodynamically stable conditions when the angle with respect to the droplet surface, termed the growth angle, is fixed. The growth angle of the NWs is determined not from a geometrical perspective but on the basis of the physical aspects of the processes occurring around the TPL, revealing a size dependence caused by the influence of linear tension of the three-phase contact of a vapor–liquid crystal. The observed radial periodic instability of the NWs is described according to the size dependence of the thermodynamic growth angle, which induces negative feedback in the system. Under the influence of linear tension and positive feedback, the tips or needles of NWs can be formed.